Assessment of Self-Piercing Riveted Joints Using the Analytic Hierarchy Process - Ebad Bagherpour (Metals, 2019)
Self-piercing riveting (SPR) as a solid-state joining technology has recently found extensive applications in the automotive industry, mostly in the joining of car body aluminium sheets. To achieve an acceptable joint, key operation and tooling parameters, including set force, die profile, and rivet shape and hardness, should be selected appropriately. To evaluate joint performance, the interlocking parameters and joint strength have to be determined. In the current laboratory and industrial practices, joint quality is assessed according to requirements of individual applications, lacking a systematic assessment method. The goal of the present study is to develop a method to determine the SPR conditions that produce a joint of the best quality, based on an analytic hierarchy process (AHP), which is a methodology for relative measurement. A general AHP model was proposed for analysing SPR and joint performance in different conditions and with an unlimited number of criteria and alternatives. Joints of two layers of 2.5 mm thick AA6082 aluminium sheets in T6 condition were produced using various dies, rivets, and SPR processing conditions. A selection of seven joints, which achieved minimum requirements in terms of interlocking parameters and strength, was nominated for AHP assessment. With the application of six criteria, including head height, bottom thickness, minimum bottom thickness, deformed rivet diameter, shear strength, and peel strength, the AHP assessment was able to define the best conditions for the SPR joining of the aluminium alloy sheets.